Cixiidae and Derbidae (Hemiptera) putative vectors of phytoplasma of group 16 SrIV - Ramos-Hernández, Eder; Lesher-Gordillo, Julia María; Ortiz-García, Carlos Fredy; Oropeza-Salín, Carlos; Sánchez-Soto, Saúl; Magaña-Alejandro, Miguel Ángel; Narváez-Cab, María del S. (Revista Colombiana de Entomología, 2020)
The phytoplasmas of the 16SrIV group cause lethal yellowing diseases (STAL) in palms worldwide. The Phytoplasma of coconut lethal yellowing (LY) has been known as 'Candidatus Phytoplasma palmae' (16SrIV-A). Like LY, many diseases caused by phytoplasma worldwide, their vectors have not been identified. The only incriminated phytoplasma vector of the LY is Haplaxius crudus (Hemiptera: Cixiidae). The objective of the present study was to determine the presence of 16SrIV phytoplasma in cixiids and derbids associated with palms (Adonidia merrillii y Cocos nucifera) positive to phytoplasmas. Captures of insects associated with these palms were made during the morning and afternoon. The presence of phytoplasma was determined by the real-time PCR using the TaqMan LY16S-ANYF (GCTAAGTCCCCACCATAACGT) and LY16S-ANYR (CGTGTCGTGAGAT-GTTAGGTTAAGT) primers; probe LY16S-ANYM (FAMCCCCTGTCGTTAATTG-NFQ). The presence of phytoplasma of the 16SrIV group was not detected in H. crudus although its presence was shown in H. skarphion (Hemiptera: Cixiidae), Oecleus snowi (Hemiptera: Cixiidae) and Persis foveatis (Hemiptera: Derbidae). These results suggest that these three species may be potential vectors of phytoplasma of group 16 SrIV in palms.